2018
DOI: 10.1308/rcsann.2017.0164
|View full text |Cite
|
Sign up to set email alerts
|

Surgery performed by supervised registrars does not adversely affect medium-term functional outcomes after total knee replacement

Abstract: Introduction Although total knee arthroplasty (TKA) is an index procedure for orthopaedic registrars, there is a lack of published research as to the effects of surgery when performed by supervised trainees. The aim of this study was to compare functional outcomes up to five years after primary TKA performed by consultants and trainee surgeons. Methods A retrospective analysis was conducted of prospectively collected data for 609 consecutive patients (339 female, 270 male) undergoing TKA. Patients were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…Given the divided nature of the existing literature, it is difficult to extrapolate the exact influence of surgeon volume and trainee status on the rate of malalignment in TKA. For example, results from studies assessing the impact of trainee surgeons and surgical experience on clinical outcomes following TKA and THA have demonstrated that neither experience nor trainee status significantly impacts outcomes [36][37][38][39] . However, similar studies assessing outcomes at U.S. Veterans Affairs (VA) training centers demonstrated mixed results 40,41 .…”
mentioning
confidence: 99%
“…Given the divided nature of the existing literature, it is difficult to extrapolate the exact influence of surgeon volume and trainee status on the rate of malalignment in TKA. For example, results from studies assessing the impact of trainee surgeons and surgical experience on clinical outcomes following TKA and THA have demonstrated that neither experience nor trainee status significantly impacts outcomes [36][37][38][39] . However, similar studies assessing outcomes at U.S. Veterans Affairs (VA) training centers demonstrated mixed results 40,41 .…”
mentioning
confidence: 99%
“…Furthermore, they found that whether a consultant or trainee had performed the procedure had no significant effect on outcomes. Other similar studies have reported that outcomes may be comparable between trainees and supervisors when operations are performed under supervision or using a navigation system [19][20][21][22]. The major difference in our study was that we compared the outcomes of more and less experienced surgeons in the same patients without the use of a navigation system.…”
Section: Discussionmentioning
confidence: 93%
“…The presence of case mix and the differential complexity levels between the groups is in fact a reflection of the reality of surgical training, as trainees should only be performing procedures appropriate to their level of training, allowing effective training to be delivered without compromising patient safety. [9] There was a high degree of heterogeneity within the dataset, particularly with respect to surgical technique. A variety of different implants were used across the studies and both conventional and navigated techniques were included.…”
Section: Discussionmentioning
confidence: 99%
“…After exclusions, a total of nine studies were included in the final analysis [4,[8][9][10][11][12][13][14][15], involving 92,309 knee arthroplasties of which 80,655 were performed by consultants, and 11,654 performed by trainees (Table 1). One of the studies was a prospective randomised controlled trial, and eight were retrospective.…”
Section: Eligible Studiesmentioning
confidence: 99%